Pemisahan Emas Pada Motherboard Komputer Dengan Metode Elektrolisis - Ricson Rinaldi; Yusnimar Yusnimar; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Gold metal has been using in electronics and telecommunication industry, for example, Motherboard computer. The separation of gold from the Motherboard computer has been done in this study. To get the maximum results in the separation of the are gold used variations potential difference ( 6; 9; 12 volt ) and the type of precipitant (NaHSO3 and H2C2O4) . In this study, a certain number of samples is used samples Motherboard computer electrolyzed H2SO4 for 1 hour. The precipitate formed is separated from the filtrate. The precipitate was dissolved in Aqua Regia at a temperature of 70˚C for 30 minutes further diluted with Aqua DM until the volume is 50 mL . Au concentration was analyzed by AAS (Atomic Absorption Spectrophotometry) and Au deposited with NaHSO3 and H2C2O4 . Based on the analysis result, the maximum Au concentration at the former Motherboard computer is equal to 2.285 ppm. For 5 grams of the sample , the maximum weight of Au precipitate obtained 0.97 grams by using H2C2O4 as a precipitant .Keywords : Au, motherboard computer, electrolisis, precipitant